Media and National Issues: Exploring Political Parallelism in Leading Pakistani Newspapers - Zarmina Gull; Dr. Syed Abdul Siraj (Journal of Peace, Development and Communication, 2023)
In political communication, media content is often parallel to political discourse. This content analysis study aims to determine whether and to what extent political parallelism exists in the coverage of major national issues published in the leading English newspapers of Pakistan. In order to identify the existence of High and Low forms of political parallelism reflected in the media content. Many parameters, such as media pluralism, media sociology, and media instrumentalization, determine existence of political parallelism in media. This study selected 11 national issues from Pakistan’s leading dailies from 1 January 2020 to 31 December 2020. The major findings revealed that political parallelism appears in selection of media content. Furthermore, the study concludes that besides politicians and industrialists, the government is also one of the influencing factors that encourage political parallelism in Pakistan.